Badania nad językiem religijnym w Polsce w latach 1988–2013. Osiągnięcia – perspektywy badawcze - Mikołajczak, Stanisław; Rybka, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
Polish linguistic research into religious language has been developing dynamically after 1988. From the beginning, they have been conducted in a wide context, and although the process of their integration is limited, it has been consistently advancing. The research in religious language in the last fifteen years have concentrated in two tightly cooperating research centres: Kraków and Poznań. Religious language, as discussed in studies published there, is widely understood as a variety of standard language used in all situations related to the sacrum. The results of research initiated and conducted by the Zespół Języka Religijnego [Religious Language Group] and the proceedings of conferences organized by the Department of the Grammar of Contemporary Polish Language of the Institute of Polish Philology at the Adam Mickiewicz University, are published in a Teolingwistika series, and in continuing volumes of Język religijny dawniej i dziś [Religious Language Now and in History]. Researchers in religious language set many tasks for themselves. They search for reasons for the contemporary crisis of religious language in Poland. They are also faced with the fact that there is no dictionary of religious language, and no synthetic study that would describe religious language in a historical perspective. Researchers also want to investigate the language of young religious persons, and of new evangelism, and the influence of contemporary media on the ongoing changes in religious communication. It is particularly important that the research is not limited to the religious language used in Catholic Church in Poland.